The state’s estate: Devaluing and revaluing ‘surplus’ public land in Canada - Whiteside, Heather (Environment and planning. A, 2019)
Since the mid-1990s, Canadian public real property (land, buildings, and equipment) has been subject to regular scrutiny through bureaucratic procedures aimed at ridding the state’s estate of all ‘surplus’ properties. Surplus is transferred to Canada Lands Company, a state owned enterprise charged with privatizing public land. Bureaucratic devaluation thus allows for subsequent revaluation through multiple forms of state-sponsored remediation: the physical, legal, and financial manipulation of public property by Canada Lands Company. Analyzing Canada Lands Company’s history, role, budgets, and activities, this article uncovers the particular dynamics of how Canadian public land is being privatized through devaluation and revaluation by the state. Two arguments of broader significance for literatures on the political economy of the state and public land frame the discussion: (1) Canada Lands Company’s activities speak to the important managerial role played by the (Canadian) state in the land dispossession process; and (2) Canada Lands Company’s treatment of surplus public land as a financial asset is a distinguishing feature of the Canadian public property management system, setting it apart from elsewhere.